Study of the Effect of the Rate of Flow of Carbon Dioxide Gas for Creation of Pneumoperitoneum on Cardiovascular System during Laparoscopic Surgeries - Meshram, Dr. Sucheta Bhowate; Gujar, Dr. Sandhya; Sidam, Dr. Karuna; Maulick, Dr. Tanumoy (International Journal of Innovative Research in Medical Science, 2016)
Laparoscopy has gained a worldwide acceptance due to its added advantages. Pneumoperitoneum required for this although aids in the surgical skill but invites a straight challenge to the attending anaesthesiologist for optimal control of haemodynamics .Reports of serious complication have been documented with abrupt and rough insufflation techniques of artificial creation of pneumoperitoneum ranging from mild bradycardia to frank cardiac arrest due to vagal mediated parasympathetic response due to rapid stretching of peritoneum. Gradual, gentle and slow rate of insufflation can prevent such complications. In this context, we have conducted a study on 40 patients of ASA I and ASA II, undergoing elective laparoscopic surgery requiring general anaesthesia with intubation. Patients were randomly allocated into study (A) and control (B) group. Group A (20 patients) comprises of the group where surgeon uses gradual and slow rate of insufflations of co2 whereas group B comprises of patients in which the surgeons uses abrupt and rapid insufflations of co2 at the rate of more than 4L/min and have found statistically significant hemodynamic changes in group B in comparison to Group A. Hence, we have concluded that insufflation with high flow rate while establishing artificial pneumoperitoneum increase IAP instantaneously and unexpected cardiovascular changes occurs such as hypotension, bradyarrhythmia whereas slow rate of insufflations prevents such complications. In patients with compromised cardio respiratory status, such vagal response with abrupt and rapid insufflations of co2 can prove to be detrimental .Therefore, not only maintaining IAP below 12-15 mmHg but also keeping slow insufflation rate (2-4lit/min) when establishing pneumoperitoneum is important and essential.